1997
DOI: 10.1046/j.1365-2168.1997.02694.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial with sequential design of laparoscopic versus conventional appendicectomy

Abstract: The laparoscopic procedure is at least as good as conventional appendicectomy. Initial laparoscopy reduces the rate of misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 15 publications
2
54
0
6
Order By: Relevance
“…Generally, the available data show no clear evidence of patient benefit after LA [8, 9, 10, 11, 12, 13, 14, 15, 16]. Most of the published studies revealed a lower wound infection rate after LA which is in fact the sole advantage [3, 4, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the available data show no clear evidence of patient benefit after LA [8, 9, 10, 11, 12, 13, 14, 15, 16]. Most of the published studies revealed a lower wound infection rate after LA which is in fact the sole advantage [3, 4, 7].…”
Section: Discussionmentioning
confidence: 99%
“…LA was revealed to be an effective procedure that could be performed in a short time. Over the years, many studies have compared OA and LA (6)(7)(8)(9)(10). In a prospective randomized study conducted by Hansen et al (6) on the effectiveness of LA, it was found that LA resulted in less wound infection, decreased analgesic need, and earlier RTNA but had a longer operation time.…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic approach for patient with suspected appendicitis improves the diagnostic accuracy and is therefore recommended. [70].…”
mentioning
confidence: 99%